Synthesis and characterization of cellulose/silica hybrid materials with chemical crosslinking - Xie, Kongliang; Yu, Yanhong; Shi, Yaqi (Carbohydrate polymers, 2009)
The cellulose/silica hybrid biomaterials are prepared by sol–gel covalent crosslinking process. The tetraethoxysilane (TEOS) as precursor, γ-aminopropyltriethoxylsilane (APTES) as couple agent, and 2,4,6-tri[(2-epihydrin-3-bimethyl-ammonium)propyl]-1,3,5-triazine chloride (Tri-EBAC) as crosslinking agent, are used in the sol–gel crosslinking process. The chemical and morphological structures of cellulose/silica covalent crosslinking hybrids are investigated with micro-FT-IR spectra, nitrogen element analysis, X-ray diffraction, SEM, AFM, and DSC. The results show that the cellulose/silica hybrids form new macromolecular structures. In sol–gel process, inorganic particles are dispersed at the nanometer scale in the cellulose host matrix, bounding to the cellulose through covalent bonds. The cellulose/silica covalent crosslinking hybrid can form good and smooth film on the cellulose. The thermal properties of organic/inorganic hybrids are improved.